1986
DOI: 10.1136/jmg.23.5.396
|View full text |Cite
|
Sign up to set email alerts
|

The frequency of the fragile X chromosome among schoolchildren in Coventry.

Abstract: A population study has been carried out among schoolchildren in the City of Coventry in order to ascertain the frequency of mental retardation associated with the fragile X chromosome. The prevalence of the fragile X mental retardation syndrome in the 11 to 16 year age group (the age of greatest ascertainment) was about 1 0 per 1000 and therefore indicates that the syndrome is a major cause of mental retardation. Estimates of the prevalence of mental retardation in males associated with the fragile X chromosom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
50
0

Year Published

1993
1993
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(54 citation statements)
references
References 8 publications
4
50
0
Order By: Relevance
“…[4] In 1986, a population study of school children in the city of Coventry gave an overall prevalence of 1/952 in males and females for fragile X syndrome. [16] Later on many of these children diagnosed as having fragile X syndrome based on cytogenetic method were found negative on molecular studies. So in 1997 a revised prevalence figure of 1/2720 males was calculated based on molecular investigations.…”
Section: Resultsmentioning
confidence: 99%
“…[4] In 1986, a population study of school children in the city of Coventry gave an overall prevalence of 1/952 in males and females for fragile X syndrome. [16] Later on many of these children diagnosed as having fragile X syndrome based on cytogenetic method were found negative on molecular studies. So in 1997 a revised prevalence figure of 1/2720 males was calculated based on molecular investigations.…”
Section: Resultsmentioning
confidence: 99%
“…[18][19] Prevalences of 0.4-0.8/1000 in males and 0.2-0.6/1000 in females were reported based on cytogenetic screening. [20][21][22][23] However, de Vries recently reported a prevalence of 0.6% by combining DNA analysis studies from Europe, Australia and the United States. 24 The frequency of new fragile X cases may.…”
Section: Discussionmentioning
confidence: 99%
“…34 Several studies published in the 1980s using the fragile site as a diagnostic tool estimated that the prevalence of the syndrome was as high as 1 in 1,500 males and 1 in 2,500 females in the general population. 35,36 The cytogenetic test employed by these studies has since been shown to be inaccurate, generating both false-negative and false-positive results. 37 The cloning of the CGG repeat responsible for the fragile X syndrome provided the opportunity for a more accurate diagnosis using molecular techniques.…”
Section: Full Mutationmentioning
confidence: 99%